2014
DOI: 10.5114/amsik.2014.47744
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of drowning using post-mortem computed tomography – state of the art

Abstract: Cel pracy: Najnowsze badania z użyciem pośmiertnej tomografii komputerowej (TK) sugerują, że metoda ta jest skuteczna w diagnozie ofiar utonięcia. W pracy podsumowano dane z literatury dotyczące efektywności diagnozowania za pomocą TK w tych przypadkach. Materiał i metody: Do przeglądu włączono badania opublikowane w latach 1999-2013, opatrzone słowami kluczowymi: "post-mortem CT scan", "drowning and CT scan", "near-drowning diagnosis" i "drowning diagnosis". Wyniki: Uwzględniono tylko 11 publikacji, których w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(109 reference statements)
0
3
0
1
Order By: Relevance
“…Skeletal chest findings and, particularly, rib fracture location and characteristics concurred (together with circumstantial data) to explain the traumatic mechanism (i.e., crushing trauma); several authors reported the strong agreement between PMCT and autopsy in the evaluation of rib fractures [ 17 , 18 ]. Clear findings were also observed on the spine, confirming the usefulness of imaging to detect both fractures and dislocation [ 16 , 19 ]. Other interesting data were found in the airway examination, in which the post-mortem imaging highlighted the presence of foreign material with different densities in both upper and lower tracts.…”
Section: Discussionmentioning
confidence: 74%
“…Skeletal chest findings and, particularly, rib fracture location and characteristics concurred (together with circumstantial data) to explain the traumatic mechanism (i.e., crushing trauma); several authors reported the strong agreement between PMCT and autopsy in the evaluation of rib fractures [ 17 , 18 ]. Clear findings were also observed on the spine, confirming the usefulness of imaging to detect both fractures and dislocation [ 16 , 19 ]. Other interesting data were found in the airway examination, in which the post-mortem imaging highlighted the presence of foreign material with different densities in both upper and lower tracts.…”
Section: Discussionmentioning
confidence: 74%
“…Las imágenes por RM de este sistema aportan datos para el hallazgo de patologías de tipo traumático (laceraciones, fisuras y roturas de órganos huecos), ocasionadas, ya sea por heridas por arma de fuego, heridas por arma cortopunzante o traumas contundentes (caídas de gran altura y golpes) (53,54), así como de tipo accidental como el ahogamiento (Figura 5); en donde, haciendo uso de los potenciadores, se muestra la abundante cantidad de líquido con partes solidas en estómago y duodeno (Figura 5b) para luego realizar la autopsia (Figura 5a) donde se ve pinzamiento de la primera porción del duodeno (flechas).…”
Section: Ahogamientounclassified
“…However, since the sinuses were aspirated blindly during autopsy, it is difficult to draw meaningful conclusions. The advent of powerful imaging technology, such as computer tomography (CT), has enabled a more robust and accurate approach to investigate fluid-filled paranasal sinuses [ 31 ], with several studies demonstrating that between 90 and 100% of suspected drowning victims exhibit the finding [ 5 , 32 36 ]. On the other hand, so do a significant proportion of non-drowned victims, where the cause of death ranges from mechanical asphyxiation (hanging) to burn and fire deaths [ 32 , 34 , 35 , 37 ].…”
Section: Introductionmentioning
confidence: 99%